2009
DOI: 10.1007/s00442-009-1476-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance dispersal helps germinating mahogany seedlings escape defoliation by a specialist caterpillar

Abstract: Herbivores and pathogens with acute host specificity may promote high tree diversity in tropical forests by causing distance- and density-dependent mortality of seedlings, but evidence is scarce. Although Lepidoptera larvae are the most abundant and host-specific guild of herbivores in these forests, their impact upon seedling distributions remains largely unknown. A firm test of the mechanism underpinning the Janzen-Connell hypothesis is difficult, even for a single tree species, because it requires more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 42 publications
(52 reference statements)
1
29
0
Order By: Relevance
“…The inclusion of a large number of naturally occurring seedlings provides the opportunity to examine both distanceand density-dependent sources of seedling mortality caused by soil-borne pathogens. Two previous experiments that explicitly manipulated naturally occurring seedling density and pathogen abundance in tropical forests reported mixed results (Bell et al 2006;Norghauer et al 2010a). Bell et al (2006) demonstrated that pathogens were a key determinant of density-dependent survival in emerging Sebastiana longicuspis seedlings, whereas Norghauer et al (2010a) did not detect pathogen-induced mortality of post-establishment seedlings of two tree species.…”
Section: Separation Of Density-and Distance-dependent Processesmentioning
confidence: 90%
See 4 more Smart Citations
“…The inclusion of a large number of naturally occurring seedlings provides the opportunity to examine both distanceand density-dependent sources of seedling mortality caused by soil-borne pathogens. Two previous experiments that explicitly manipulated naturally occurring seedling density and pathogen abundance in tropical forests reported mixed results (Bell et al 2006;Norghauer et al 2010a). Bell et al (2006) demonstrated that pathogens were a key determinant of density-dependent survival in emerging Sebastiana longicuspis seedlings, whereas Norghauer et al (2010a) did not detect pathogen-induced mortality of post-establishment seedlings of two tree species.…”
Section: Separation Of Density-and Distance-dependent Processesmentioning
confidence: 90%
“…Two previous experiments that explicitly manipulated naturally occurring seedling density and pathogen abundance in tropical forests reported mixed results (Bell et al 2006;Norghauer et al 2010a). Bell et al (2006) demonstrated that pathogens were a key determinant of density-dependent survival in emerging Sebastiana longicuspis seedlings, whereas Norghauer et al (2010a) did not detect pathogen-induced mortality of post-establishment seedlings of two tree species. Our natural field experiments suggested that fungal pathogens did accelerate the mortality of seedlings in a subtropical forest but that the effect of pathogens on mortality is independent of seedling density.…”
Section: Separation Of Density-and Distance-dependent Processesmentioning
confidence: 90%
See 3 more Smart Citations